Analysis of Students Mathematical Communication Ability Models on Set Materials - Iryono, Mustofa Baydillah; Qonita, Indy; Elya M, Syifa Ratna (Etunas Sukses Sistem, 2022)
This study aims to see and analysis: The ability of mathematical communication to connect actual items, photos and diagrams into mathematical thinking. The ability of mathematical communication to provide explanations for thoughts, conditions, writing with gadgets, pictures, graphs, and actual algebra. The ability to speak mathematically expresses ordinary events in language or mathematical symbols. The ability of mathematical conversation to create state versions through writing, concrete gadgets, pictures, graphs, and algebraic methods. Mathematical verbal exchange ability to provide explanations and make questions about mathematics that has been found. The method in this study uses a qualitative method. The results showed that the mathematical communication ability to connect real objects, pictures and diagrams became low mathematical inspiration. Mathematical communication skills mentioning ideas, situations, writing using real objects, pictures, graphs and algebra are classified as moderate. Mathematical communication ability models states that everyday occurrences in mathematical language or symbols are low. The ability of mathematical communication to produce examples of a situation through writing, real objects, pictures, graphs, and algebraic methods is low. The ability of mathematical communication to express and make questions about the mathematics that has been learned is low.